Transformation of Sherpa Livelihoods, Resilience, and Sustainability in the Everest Region of Nepal - Bhattarai, Utsab (Dhaulagiri Journal of Sociology and Anthropology, 2025)
This study explores Everest tourism's role in building resilience and reshaping livelihoods of Sherpa households in the two settlements- Namche Bazaar and Thulo Gumela in the Everest (Khumbu) region of the Nepal Himalaya. Employing a comprehensive framework that integrates economic, social, cultural, and environmental facets, this research primarily scrutinizes the primary data gathered through face-to-face interviews, key informant interviews, and focus group discussions, with an equal number of participants from each study site. The findings reveal a significant disparity in terms of economic opportunities. Namche Bazaar, strategically located along the main trail of Khumbu to Everest Base Camp, benefits substantially from Everest tourism. Whereas Thulo Gumela, situated off the main route, faces economic disadvantages and limited access to local tourism initiatives. While both villages share similar social, cultural, and environmental influences of tourism, notable discrepancies emerge between them. These differences are largely driven by the exponential growth of tourism in the region, the establishment of Sagarmatha National Park, and the rapid rise in visitor numbers. They are further shaped by unequal access to tourism opportunities and the broader influences of modernization and technological advancement. These interconnected and underlying forces have reshaped Sherpa livelihoods, stimulating their resilience and adaptive capacities, creating both opportunities and challenges. The study offers policymakers and development practitioners insightful information, advocating strategic tourism planning and management for Khumbu. The study highlights acknowledging and promoting potential tourism products of underrepresented villages like Thulo Gumela. This approach helps promote equitable economic growth across all villages of Khumbu while safeguarding Sherpas’ unique sociocultural heritage and rich biodiversity, thereby offering opportunities for all communities within this historic region to benefit from tourism.